Economic Voting in EU Referendums: Sociotropic versus Egocentric Voting in the Lisbon Treaty Plebiscites in Ireland - Elkink, Johan A. (2019)
Economic voting is one of the most studied aspects of electoral behaviour. The dominant view is that sociotropic economic considerations are more important to voters in national elections. However, other research suggests that utilitarian motivations are key to understanding support for the EU. An EU integration referendum offers the opportunity to explore whether and when sociotropic or utilitarian motivations are more important in determining vote choice. The unusual combination of two successive referendums in Ireland on the Lisbon Treaty, either side of the global financial crisis, provides the ideal opportunity to test these assumptions. Using data from two post-referendum surveys, we demonstrate that the economy mattered in both referendums but that different economic motivations drove vote choice in each, with sociotropic motivations more critical as a result of the global financial crisis. Our study has implications for economic voting and referendums and demonstrates that context is crucial in determining a voter’s economic motivations in a plebiscite.